PENGARUH PENERAPAN MODEL READING TO LEARN (R2L) TERHADAP KEMAMPUAN LITERASI MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 6 SAWAHLUNTO - Dewanti, Afifah (Departemen Matematika, 2023)
Everyone must be more literate in today's competitive society. Mathematical literacy is crucial during educational disruption. According to PISA data, Indonesian students' mathematical literacy skills are still substantially lower than the global average. A new teaching technique has been used to improve Indonesian students' mathematical literacy. This study examined how the Reading To Learn (R2L) model improved math literacy. The non-equivalent posttest alone control group design was utilized in this quasi-experimental study. This survey sampled 60 class IX SMPN 6 Sawahlunto students. The final test results demonstrated that the R2L paradigm improved mathematical literacy.Keyword: Mathematical Literacy, Learning Model, Reading to Learn (R2L)